Pengaruh Strategi Marketing Flashsale E - Commerce Terhadap Perilaku Konsumen dalam Berbelanja Ditinjau dari Perilaku Impulsivebuying: Study Case Tokopedia - Silviya Qotrunnada (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The development in the world of technology has provided convenience in the business sector, where business players find it easier to promote goods and services. Supported by the emergence of various platforms that can be used as one of the strategies in selling products and services, such as marketplaces. In Indonesia alone, there are already dozens of marketplaces recognized by the public, such as Shopee, Tokopedia, Bukalapak, Lazada, and others. Furthermore, these marketplaces also implement promotional strategies to be more attractive to buyers, one of which is flash sales. Flash sales often influence consumers to make unplanned purchases, commonly known as impulsive buying. This research will discuss the influence of flash sale marketing strategy in e-commerce on consumer behavior in shopping, focusing on impulsive buying behavior on one marketplace, Tokopedia. In 2021, Tokopedia was the marketplace with the highest number of visitors and is still one of the nation's marketplaces that has survived until now. This study uses a quantitative method with data collection using questionnaires and analyzed using SPSS with multiple linear regression models. There are four independent variables: product factors, price discounts, free shipping, and brand image, and the dependent variable is impulsive buying. The conclusion of this research is that product factors, price discounts, free shipping, and brand image have a significant effect on impulsive buying during flash sales on Tokopedia.